2013
DOI: 10.1289/ehp.1205221
|View full text |Cite
|
Sign up to set email alerts
|

In Utero Exposure to Dioxins and Dioxin-like Compounds and Anogenital Distance in Newborns and Infants

Abstract: Background: Anogenital distance in animals is used as a measure of fetal androgen action. Prenatal exposure to dioxins and dioxin-like compounds in rodents causes reproductive changes in male offspring and decreases anogenital distance.Objective: We assessed whether in utero exposure to dioxins and dioxin-like compounds adversely influences anogenital distance in newborns and young children (median age, 16 months; range, 1–31 months).Methods: We measured anogenital distance among participants of the “Rhea” mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 55 publications
(83 reference statements)
1
32
0
Order By: Relevance
“…However, these effects were often transient and their clinical relevance discussed (Koopman-Esseboom et al 1994, 1996; Pluim et al 1993; Weisglas-Kuperus et al 1995, 2000, 2004). Very recently, a study from Spain and Greece reported a negative relationship between maternal levels of DL compounds and anogenital distance in newborns (Vafeiadi et al 2013). Many of these studies could not differentiate between possible effects of DL compounds (in TEQ) or PCBs due to their simultaneous occurrence in human milk.…”
Section: Discussionmentioning
confidence: 99%
“…However, these effects were often transient and their clinical relevance discussed (Koopman-Esseboom et al 1994, 1996; Pluim et al 1993; Weisglas-Kuperus et al 1995, 2000, 2004). Very recently, a study from Spain and Greece reported a negative relationship between maternal levels of DL compounds and anogenital distance in newborns (Vafeiadi et al 2013). Many of these studies could not differentiate between possible effects of DL compounds (in TEQ) or PCBs due to their simultaneous occurrence in human milk.…”
Section: Discussionmentioning
confidence: 99%
“…Sex-specific results in our study and others suggest greater susceptibility of male infants to the effects of environmental contaminants with dioxin-like activity. 37,53 Some experimental animal studies support this hypothesis, including sex-specific transgenerational effects on the reproductive system. 54 the mechanisms through which growth restriction induced by in utero dioxin exposure might be more pronounced in boys remain unclear.…”
Section: Figurementioning
confidence: 93%
“…35 Pregnant women were enrolled from 2006 to 2010 in 11 maternity units located in copenhagen, Denmark; Heraklion, greece; Oslo and akershus, norway; Barcelona and Sabadell, Spain; and Bradford, england. [36][37][38][39][40][41] all research procedures were approved by the local ethical committees, and written informed consent was obtained from all women participating in the studies. rules for ethical conduct are stated in the technical annex to the contract with the eU commission (contract no.…”
Section: Study Populationmentioning
confidence: 99%
“…Exposure in utero has been related to a number of adverse health endpoints in children, including a higher risk for overweight, alterations in psychomotor and cognitive development or urogenital abnormalities in male newborns (Forns et al 2012; Palmer et al 2009; Puertas et al 2010; Valvi et al 2013), and several studies have reported sex specific effects occurring by mechanisms that remain poorly understood (Fernandez et al 2007; Papadopoulou et al 2013; Vafeiadi et al 2013; Valvi et al 2012 ).…”
Section: Introductionmentioning
confidence: 99%